3D printing of biomimetic multi-layered GelMA/nHA scaffold for osteochondral defect repair. (5th June 2019) - Liu, Jingyi; Li, Liang; Suo, Hairui; Yan, Mengling; Yin, Jun; Fu, Jianzhong
Abstract: Currently, osteochondral defects frequently cause limited motion and impaired function of the joint, leading to serious healthcare problems, and it is still very challenging to realize the simultaneous regeneration of subchondral bone with cartilage. In the current study, we designed a tri-layered scaffold and fabricated it using the extrusion-based multi-nozzle 3D printing technology. The bioinks used for 3D printing included a 15% methacrylated gelatin (GelMA) hydrogel for cartilage on top layer, a combination of 20% GelMA and 3% nanohydroxyapatite (nHA) (20/3% GelMA/nHA) hydrogel for interfacial layer, and a 30/3% GelMA/nHA hydrogel for subchondral bone at bottom layer. The water absorption capacity, biodegradation, and mechanical properties of hydrogels and scaffolds were characterized, and in vitro assay with bone marrow mesenchymal stem cells (BMSCs) was performed to indicate the biocompatibility of scaffolds. Based on the results of in vivo repair of rabbit osteochondral defect, the neo-tissues in defects integrated better with the surrounding tissues, the joint surface of the defects was smoother, and more cartilage-specific extracellular matrix and collagen type II were observed using the tri-layered scaffolds. This study not only provides a potential manufacturing method for multi-layered scaffolds, but also is helpful for understanding the regeneration mechanism of cartilage-subchondral bone. Graphical abstract: Unlabelled Image Highlights: A functionally graded osteochondral scaffold was manufactured using GelMA/nHA hydrogels by extrusion-based 3D printing The scaffold manufacturing process was simple and efficient without additional postprocess The scaffolds have appropriate swelling ratio, biodegradation rate, mechanical properties, and excellent biocompatibility The tri-layered GelMA/nHA scaffolds showed promising in vivo results of rabbit osteochondral defect repair